Intraocular Plasmablastic Lymphoma in a HIV Patient - Carolline Fontes Alves Mariano; Glauce Lunardelli Trevisan; Antonio Augusto Velasco e Cruz; Fernando Chahud (Hindawi Limited, 2017)
Plasmablastic lymphoma (PBL) is a rare B-cell lymphoma occurring mainly in HIV patients. The tumor frequently involves extranodal sites such as the oral cavity, nasal cavity, gastrointestinal tract, skin, and lungs. The neoplastic cells are characterized by a plasmablastic appearance and typical immunophenotype that indicates plasma cell differentiation. Herein, we report a case of intraocular involvement by plasmablastic lymphoma in a HIV patient with a long history of cytomegalovirus retinitis and loss of vision. After an evisceration performed to control the blind, painful eye a diagnosis of PBL was made by examining the eye contents. Two months later, a biopsy of cervical lymph node revealed nodal lymphoma of the same type. To the best of our knowledge, this is the second case of intraocular PBL reported in English literature.